2020
DOI: 10.1021/acsami.0c16914
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Broadband Nanoporous Semiconductor Photonic Crystals for Visible-Light-Driven Photocatalysis

Abstract: Published Work), and on Private Research Collaboration Groups under the following conditions:  It is mandated by the Author(s)' funding agency, primary employer, or, in the case of Author(s) employed in academia, university administration.  If the mandated public availability of the Accepted Manuscript is sooner than 12 months after online publication of the Published Work, a waiver from the relevant institutional policy should be sought. If a waiver cannot be obtained, the Author(s) may sponsor the immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 60 publications
0
27
0
1
Order By: Relevance
“…As such, it is critical to determine the red boundary position of TiO 2 –NAA-DBRs’ PSB in water, since this is the spectral region where incident photons interact with the semiconductor coating to generate charge carriers involved in photocatalytic reactions. Red-boundary slow light increases the number of photon-to-semiconductor interactions in these photonic structures, enabling a means of harnessing this optoelectronic phenomenon to boost photocatalytic rates. , The red boundary of TiO 2 –NAA-DBRs’ PSB is estimated using eq …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, it is critical to determine the red boundary position of TiO 2 –NAA-DBRs’ PSB in water, since this is the spectral region where incident photons interact with the semiconductor coating to generate charge carriers involved in photocatalytic reactions. Red-boundary slow light increases the number of photon-to-semiconductor interactions in these photonic structures, enabling a means of harnessing this optoelectronic phenomenon to boost photocatalytic rates. , The red boundary of TiO 2 –NAA-DBRs’ PSB is estimated using eq …”
Section: Resultsmentioning
confidence: 99%
“…, PSB’s red and blue boundary, respectively) dielectric parts of the PC’s structures is strongly reduced. Slow light localized at the PSB’s red edge increases the number of interactions between photons and semiconductor within PC structures, enabling additional light-induced generation of e – –h + pairs by ALD-deposited TiO 2 coatings on the nanopores of NAA-DBRs. , To elucidate photocatalytic enhancements associated with slow light, we analyzed optical alignment of MB’s band and PSB’s red boundary of TiO 2 –NAA-DBRs with a combinational variation of anodization period and functional coating deposition time in water and correlated these with their corresponding k values (Figure a–c and Table S1Supporting Information). Analysis of λ PSB‑red of TiO 2 –NAA-DBRs with t TiO 2 = 0.5, 1, and 2 nm indicated that λ PSB‑red remains practically constant ( i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the 1D-PC, Santos's group presented an ideal photocatalyst platform that consists of TiO 2functionalized nanoporous anodic alumina broadband DBR (Figure 12a). [25,61,189,190] Photocatalytic performance decreased when the red edge of the photonic stop bands was shifted to the visible wavelengths, while a photocatalytic performance increment was achieved when the red edge of photonic stop bands was positioned within the organic absorption band.…”
Section: Photonic Crystal Cavitymentioning
confidence: 99%
“…Taking advantage of the unique optical properties, such as high-quality factor (Q-factor) and small mode volume, optical resonators offer a promising platform to enhance the lightmatter interactions in many areas, such as lasers, integrated photonics, photodetectors, optical sensors, biomedical detection, and photoenergy-related devices. [8][9][10][11][12][13][14][15][16] To date, many types of optical resonators have been applied in both photovoltaic and photocatalysis, including Fabry-Perot (FP) cavities, [17][18][19] whispering gallery mode (WGM) cavities, [20][21][22] photonic crystal (PC) cavities, [23][24][25] plasmonic resonators (Figure 1). [26][27][28] From an optics point of view, these optical resonant configurations exhibit strong optical feedback and photons confinement, which has the great potential to solve the intrinsic tradeoff between light absorption and carrier diffusion.…”
Section: Introductionmentioning
confidence: 99%